Analisis Pengaruh Pelatihan dan Pengembangan, Kompensasi serta Kompetensi Terhadap Kinerja Karyawan J&T Express di Kota Bima - Syafitrah, Anas; Ikbal Irawan; Yusuf, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of training and development, compensation, and competence on the performance of J&T Express employees in Bima City. The study used a quantitative approach with an associative design. The study population was 67 J&T Express employees in Bima City, with a sample of 34 respondents determined using a purposive sampling technique. Primary data were collected by distributing Likert-scale questionnaires to employees who met the research criteria. Data analysis was carried out using multiple linear regression with the help of SPSS version 22, which began with a validity test, reliability test, normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing was carried out through t-test, F-test, and coefficient of determination (R²). The results showed that compensation and competence had a positive and significant effect on employee performance, with significance values ​​of 0.016 and 0.021 (<0.05), respectively. Conversely, training and development did not have a significant effect on employee performance with a significance value of 0.175 (>0.05). Simultaneously, training and development, compensation, and competence significantly influence employee performance with an F-value of 12.754 and a significance level of 0.002 (<0.05). These variables explain 21.6% of the variation in employee performance, while the remainder is influenced by factors outside the research model.